Analisis Kinerja Keuangan pada Perusahaan Daerah Air Minum (PDAM) Sebelum dan Selama Pandemi Covid-19 (Studi Kasus PDAM Tirta Dharma Batanghari Periode 2017-2021) - Siti Umami Khikmah; Sintya Dame Kristin S; Ratih Kusumastuti (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
As one of the Regional Owned Enterprises (BUMD), the main function of the regional drinking water company (PDAM) is a social function, namely providing and distributing clean water to the community. In addition, the PDAM must also gain profits so that operational activities can be sustainable and increase regional income. To measure sales of this function, an analysis of the PDAM's financial performance is carried out. The purpose of this study was to determine the health and financial performance of PDAM Tirta Batanghari from 2017 to 2021 before, during and after Covid-19. This type of research is quantitative research with documentation studies. The results of this study indicate that the PDAM's financial performance for 5 years has obtained good management costs, is liquid in fulfilling current liabilities but the profit earned has not been stable.